MYOPIA AND ITS COMPLICATIONS - Fayzullayeva Gavhar Jamoljonovna (KONFERENSIYALAR, 2025)
Аnnotation. This review explores current views on the causes and development of complications related to myopic refraction. It summarizes domestic and international research using modern diagnostics and highlights that myopia involves not only refractive and anatomical changes, but also pathological processes linked to disrupted ocular hemodynamics and hydrodynamics.